Pregnancy Morbidities in Korean Patients with Takayasu Arteritis: A Monocentric Pilot Study - Pyo, Jung Yoon; Song, Jason Jungsik; Park, Yong-Beom; Lee, Sang-Won (Yonsei medical journal, 2020)
We investigated pregnancy morbidities in Korean patients with Takayasu arteritis (TA) in a single tertiary hospital as a pilot study. We retrospectively reviewed the medical records of 12 pregnancies in seven patients with TA. All patients were diagnosed with TA based on the 1990 American College of Rheumatology classification criteria. The medical records of patients were well-documented, allowing review of clinical data including pregnancy morbidities. The angiographic and Ishikawa classifications at diagnosis and TA activity at delivery were assessed. Of the 12 pregnancies, two pregnancies ended in spontaneous abortion (16.7%), and one pregnancy (8.3%) had therapeutic abortion at 9 weeks due to maternal morbidity. Among the remaining nine pregnancies, only one child was delivered via normal spontaneous vaginal delivery, and the remaining eight were delivered by Caesarean section. Two out of nine (22.2%) neonates were born with low birth weight, and one of them was born at 30 weeks of gestation. The most common maternal complication was hypertension affecting 7/12 (58.3%) pregnancies. Preeclampsia occurred in one pregnancy, and gestational diabetes mellitus (GDM) occurred in two pregnancies. At delivery, disease activity of TA was stable in all pregnancies, and glucocorticoids were administered in nine pregnancies. Live birth rate of pregnant Korean patients with TA was 75%. Future studies are needed to reduce pregnancy-related complications.We investigated pregnancy morbidities in Korean patients with Takayasu arteritis (TA) in a single tertiary hospital as a pilot study. We retrospectively reviewed the medical records of 12 pregnancies in seven patients with TA. All patients were diagnosed with TA based on the 1990 American College of Rheumatology classification criteria. The medical records of patients were well-documented, allowing review of clinical data including pregnancy morbidities. The angiographic and Ishikawa classifications at diagnosis and TA activity at delivery were assessed. Of the 12 pregnancies, two pregnancies ended in spontaneous abortion (16.7%), and one pregnancy (8.3%) had therapeutic abortion at 9 weeks due to maternal morbidity. Among the remaining nine pregnancies, only one child was delivered via normal spontaneous vaginal delivery, and the remaining eight were delivered by Caesarean section. Two out of nine (22.2%) neonates were born with low birth weight, and one of them was born at 30 weeks of gestation. The most common maternal complication was hypertension affecting 7/12 (58.3%) pregnancies. Preeclampsia occurred in one pregnancy, and gestational diabetes mellitus (GDM) occurred in two pregnancies. At delivery, disease activity of TA was stable in all pregnancies, and glucocorticoids were administered in nine pregnancies. Live birth rate of pregnant Korean patients with TA was 75%. Future studies are needed to reduce pregnancy-related complications.